Pengaruh Kualitas Produk, Citra Merek Dan Electronic Word of Mouth Terhadap Keputusan Pembelian Sangkar Ebod Jaya - Heru Wijaya; Herni Justiana Astuti; M Agung Miftahuddin; Suyoto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to evaluate the influence of product quality, brand image, and electronic word of mouth on the purchase decision of Ebod Jaya bird cages. The population in this study consisted of 160 bird competition participants in Purbalingga Regency. The sampling technique used was non-probability sampling, resulting in a total of 109 respondents successfully collected. Data analysis was carried out using the Structural Equation Modeling (SEM) approach with the assistance of SmartPLS version 4.0. The analysis in this study consisted of two main parts: the outer model and the inner model. The outer model testing included assessments of convergent validity, discriminant validity, and reliability to ensure the quality of the research instruments. Meanwhile, the inner model was used to assess the relationships between constructs, including hypothesis testing, R-square (R²) values, and goodness of fit. Hypothesis testing aimed to determine the significance of the influence of independent variables on the dependent variable. The results of the study indicate that electronic word of mouth has a positive and significant effect on purchase decisions. In contrast, product quality and brand image variables do not have a partial effect on purchase decisions. These findings are expected to provide valuable input for Ebod Jaya's management in formulating more effective strategies and marketing mixes to improve sales target achievement.